SMART: Towards spatial internet marketplaces - David J. Abel; Volker Gaede; Kerry L. Taylor; Xiaofang Zhou (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
Spatial Internet Marketplaces are attractive as a mechanism to enable spatial applications to be built drawing on remote services for supply of data and for data manipulation. They differ from the usual distributed systems by treating the services as published by providers on the Internet and bought by customers on an as-required basis. Design ofa Spatial Internet Marketplace essentially seeks to overcome the problems of heterogeneity in large collections of autonomously-provided resources while avoiding complex requirements for publication. The architecture for a marketplace is considered in terms of the components required and the special issues in constructing an infrastructure for a Spatial Internet Marketplace. We initially describe the SMART (Spatial Marketplace) basic model, with its four service types of query, function, planning and execution services and different message types. A prototype application, the ACT-TAP system, is sketched to demonstrate an application of the SMART model. Some desirable extensions to the basic model to expand its functionality are considered. Finally we consider some important open research questions for marketplaces.
urn:nbn:de:kobv:11-10064316
Keywords: 330